CCR2 Positive Exosome Released by Mesenchymal Stem Cells Suppresses Macrophage Functions and Alleviates Ischemia/Reperfusion-Induced Renal Injury - Bing Shen; Jun Liu; Fang Zhang; Yong Wang; Yan Qin; Zhihua Zhou; Jianxin Qiu; Yu Fan (Hindawi Limited, 2016)
Mesenchymal stem cells (MSCs) derived exosomes have been shown to have protective effects on the kidney in ischemia/reperfusion-induced renal injury. However, the key components in the exosomes and their potential mechanisms for the kidney protective effects are not well understood. In our current study, we focused on the abundant proteins in exosomes derived from MSCs (MSC-exo) and found that the C-C motif chemokine receptor-2 (CCR2) was expressed on MSC-exo with a high ability to bind to its ligand CCL2. We also proved that CCR2 high-expressed MSC-exo could reduce the concentration of free CCL2 and suppress its functions to recruit or activate macrophage. Further, knockdown of CCR2 expression on the MSC-exo greatly abolished these effects. Finally, we also found that CCR2 knockdown impaired the protective effects of MSC-exo for the renal ischemia/reperfusion injury in mouse. The results indicate that CCR2 expressed on MSC-exo may play a key role in inflammation regulation and renal injury repair by acting as a decoy to suppress CCL2 activity. Our study may cast new light on understanding the functions of the MSC-exo and these receptor proteins expressed on exosomes.